Hyperglicemia as Predisposition Factor of Oral Candidiasis on patient with Diabetes Mellitus - Dian Nurmansyah; Elma Stasya; Dewi Ramadhani; Normaidah Normaidah; Aldiana Astuti (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Diabetes mellitus is a disease characterized by hyperglycemia or an increase in blood glucose levels. The state of hyperglycemia is one of the supporting factors for oral candidiasis infection. The purpose of this study was to determine the correlation of hyperglycemia with the incidence of Candida albicans infection in patients with Diabetes mellitus. this study was conducted on 30 respondents. Blood glucose levels and Candida albicans culture were measured using the germ tube test method. Data analysis to see the correlation using the Chi-Square test obtained Sig. (0.015 0.00.050) and it can be stated there is a correlation between variables. From the results of data analysis, it can be concluded that there is a correlation between hyperglycemia and Candida albicans infection which causes oral candidiasis in DM patients.